Public health implications of the re-emergence of ‘Chandrabora’ or ‘Ulobora’ (Russell’s viper) envenoming in Bangladesh - Amin, Md Robed; Ghose, Aniruddha; Rahman, Akm Fazlur; Kuch, Ulrich; Faiz, Md Abul (Bangladesh Journal of Medicine, 2024)
Abstract not available Bangladesh J Medicine 2024; 35: 129-132